Profitability, investment and average returns - Fama, Eugene F.; French, Kenneth R. (Journal of Financial Economics, 2006)
Valuation theory says that expected stock returns are related to three variables: the book-to-market equity ratio (Bt/Mt), expected profitability, and expected investment. Given Bt/Mt and expected profitability, higher expected rates of investment imply lower expected returns. But controlling for the other two variables, more profitable firms have higher expected returns, as do firms with higher Bt/Mt. These predictions are confirmed in our tests.